Penerapan Arsitektur Regionalisme Pada Perancangan Ruang Dan Tampilan Bangunan Museum Al-Qur'an Di Kota Malang - Sudartian, Marlina Trendy; Paturusi, Syamsul Alam; Rajendra, I Gusti Ngurah Anom (Jurnal Arsitektur Universitas Udayana; Vol 10 No 02 (2022): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v10i02.85991, 2022)
The Qur'an is a holy book as a guide and guide for Muslims who believe and are pious in carrying out life, so that humans are required not only to study but must know the history of Islam regarding the Qur'an in the city of Malang which is dubbed the city of history. and student city. In the application related to the design of the Al-Qur'an museum with the Regionalism Architecture approach, it begins by using a combination of qualitative and quantitative research methods in the flow of data collection as input which is then processed through systematic stages into project specifications as output. Therefore, the design of the Al-Qur'an Museum with a regionalist architectural approach will make it easier for the public to learn about the history of Islam about the Qur'an. The architectural approach of regionalism is regionalism as a cultural system, regionalism as a soul in a place and regionalism as an identity and regionalism as a critical attitude. The geometric shape of the building, which is a rectangle, is then put together according to the needs and zoning of the space and the materials used and the appearance of the building which will affect the identity and function of the building. Keywords: perancangan, museum, regionalism architecture, Qur’an